(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This paper explores the application of Project-Based Learning (PBL) in teaching English for tourism students. The tourism industry requires professionals who can communicate effectively in English and solve real-life problems creatively. Therefore, PBL provides a learner-centered framework that integrates language skills with practical, tourism-related projects. The paper discusses theoretical foundations, implementation strategies, challenges, and pedagogical benefits of PBL in English for Tourism (EFT) contexts. The findings suggest that PBL enhances language proficiency, critical thinking, collaboration, and intercultural competence, making it an effective method for preparing students for real-world communication in tourism